(Not) good mechanism of the Presidency, i.e. the problem of leadership in the European Union in the period 1957–2017 (Economic and Political Thought, 2018)
The purpose of this paper is to present the process of shaping and reformingof the mechanism of the Presidency of the Council from the adoptionand ratification of the Treaty of Rome to the Lisbon reform.The founding fathers, as well as the later initiators and creators of theTreaties establishing the Communities and the European Union, did notassign a major role to the Presidency of the Council. On the one hand, thepresidency of the Community and then of the EU institutional structurewas treated as a kind of ‘technical’ instrument for managing the variousconfigurations of the Council and preparatory bodies for a specific time andin a fixed sequence. On the other hand, the Presidency was perceived bythe Member States as a formal expression of equality of all members of theEuropean Union. However, it should be noted that, with the growth in theprocesses of enlargement and deepening of the European integration, theposition and role of the Presidency as a mechanism for the functioning ofthe European Union continued to grow. Over time, new plans and proposalshave been made to streamline this mechanism to preserve the managementcontinuity and increase the effectiveness of decision-making in the EuropeanUnion.The main function of the Presidency of the Council is to set the agendafor the Union’s action, to manage the work of the Council and its subsidiarybodies, to represent the Council in relations with other Union institutionsand bodies, and also to represent the Union in relations with third countriesand international organizations.Thus, the Presidency of the Council de facto consists in compromising inthe course of work of the EU institutions and bodies, as well as working outand making decisions in a more abundant group of Member States. Therefore,the Presidency of the Council is a formal expression of their equality.Analysing the history of the development of the Presidency of the Councilmechanism, one can say that it evolved along with the process of deepeningintegration and enlarging the Communities, and later the European Union,and was shaped by these processes. Over the past 60–65 years, it has repeatedlychanged to adapt to the new conditions, challenges and threats to theEuropean integration.
Keywords: European integration, the European Communities, the European Union, the Presidency of the Council